Strategi Sosialisasi KPU dalam Meningkatkan Partisipasi Politik Masyarakat Muslim di Kota Magelang pada Pilkada 2024: Studi Perspektif Budaya Politik Islam - Tafrika Donita; Martien Herna Susanti (Kartika: Jurnal Studi Keislaman, 2025)
This research investigates the strategy of the General Election Commission (KPU) of Magelang City in enhancing political participation among Muslim communities during the 2024 Regional Head Election (Pilkada). The phenomenon observed reveals a growing concern regarding the declining political engagement, particularly among young Muslim voters, in an era dominated by digital communication and apathy. The study aims to analyze how the KPU formulates and implements socialization strategies aligned with Islamic political culture, which includes Islamic values as sources of ethics, democracy as a political framework, and both cultural and institutional factors. Using a qualitative descriptive method, data were collected through interviews, documentation, and observation. Analysis was carried out using the Miles and Huberman model and triangulation for data validation. The findings reveal that KPU Magelang applied a segmented and integrative communication strategy digital, participative, and conventional tailored to different voter age groups. Notably, the incorporation of religious and ethical messaging, community-based education, and collaboration with youth organizations significantly contributed to increased participation, with turnout reaching 79.16% in 2024. This study underscores the relevance of contextualized Islamic political culture in fostering democratic engagement within Muslim-majority regions.